Introduction to the Symposium on Science, Religion, and the Rise of Biblical Criticism - Ungureanu, James C. (Zygon, 2021)
This is an introduction to the Symposium on “Science, Religion, and the Rise of Biblical Criticism,” which has been designed as a thematic section for Zygon: Journal of Religion and Science. The Symposium demonstrates the importance of and need for greater interdisciplinary collaboration between philosophers, theologians, scholars of religion, and historians in tracing the origins and development of the “conflict thesis” between science and religion. Often neglected is the role biblical criticism played in guiding and constructing narratives of conflict. This series of articles thus attempts to redress this gap in the scholarship by explicitly focusing on the advent of historical-critical scholarship of the Bible and how it changed perceptions about “science” and “religion.”